LEARNING ENVIRONMENT SUPPORT FOR STUDENT ONLINE LEARNING AT SMK NEGERI 1 PAINAN - Rizky Yulis Putra; Sri Arita (Sean Institute, 2022)
This study aims to describe the support of the learning environment for courageous learning at SMK Negeri 1 Painan. This type of research is descriptive research. The population in this study were all students at SMK N 1 Painan, as many as 201 people, and a sample of 68 people. The results of this study indicate that 1) The average score of the school environment support aspect, which consists of 10 questions, where the average value is 4.09 with a Respondent Attainment Level (TCR) of 81.71%, according to theory, if the TCR ranges from 81 – 100% = Very Good. This shows that school environmental support is in the Very Good category. The average score for the support aspect of the family environment consists of 10 questions. The average value is 4.26, with a Respondent Attainment Level (TCR) of 85.21%. According to theory, if the TCR ranges from 81 – 100% = Very good. This shows that family environment support is in the Very Good category. The average score of the peer support environment aspect consists of 10 questions, where the average value is 4.07 with a Respondent Attainment Level (TCR) of 81.47%, according to theory if the TCR ranges from 81 – 100% = Very Good. This shows that family environment support is in the Very Good category.